Working Paper 54: Targeting illicit wealth through non-conviction based forfeiture: Identifying human rights and other standards for Latin America (Basel Institute on Governance Working Papers, 2024)
This paper explores the wide variety of non-conviction based (NCB) forfeiture laws in Latin America, with a special focus on the region’s predominant model, Extinción de dominio. It argues that NCB forfeiture legislation, which allows for the recovery of stolen assets outside of criminal proceedings, can contribute significantly to a state’s policy response to rampant economic and organised crime. The paper emphasises the importance of critically reviewing and harmonising domestic practices of NCB forfeiture aroundemerging standards, so that they can reach their large potential. Ensuring their alignment with international human rights and other recognised norms and rules ultimately builds trust, lends legitimacy and fosters judicial cooperation in international NCB forfeiture cases. About this reportThis paper is published as part of the Basel Institute on Governance Working Paper series, ISSN: 2624-9650. You may share or republish the Working Paper under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND 4.0).Suggested citation: Solórzano, Oscar. 2024. ‘Targeting illicit wealth through non-conviction based forfeiture: Identifying human rights and other standards for Latin America.’ Working Paper 54, Basel Institute on Governance. Available at: baselgovernance.org/publications/wp-54.DisclaimerThis Working Paper is intended for general informational purposes and does not constitute and/or substitute legal or other professional advice. The contents are the sole responsibility of the author and do not necessarily reflect the views and the official position of the Basel Institute on Governance, its donors and partners, or the University of Basel.
Keywords: Asset recovery; Latin America; non-conviction based forfeiture; Extinción de dominio; human rights; international norms; financial crime; organised crime; illicit enrichment; civil recovery; Peru